Load and wear of automatic couplers in locomotive traction passenger car - A. V. Belyankin; V. V. Balakin; V. K. Meshkov; M. A. Fedorov (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. A number of design features of the rolling stock and operating conditions of the SA-3 automatic coupler in locomotive traction passenger cars cause increased wear of the rubbing surfaces of the automatic coupler, which requires measures to strengthen them. The issue of automatic coupler loading for wagons is studied and presented in research, technical and regulatory documentation. The authors consider the experimental data on longitudinal forces and relative displacements of automatic couplers under operating modes to be insufficient in the case of the SA-3 automatic coupler in a locomotive traction passenger car. Lack of such studies did not allow manufacturers of SA-3 automatic couplers intended for use in passenger rolling stock to reasonably implement processes for hardening of contact surfaces. The study was primarily intended to obtain reliable experimental data on the relative displacements of automatic couplers during motion as part of a passenger train, as well as on the acting longitudinal forces.Materials and methods. The main method of the research was direct measurements of relative displacements using contact displacement sensors. Longitudinal forces were determined by resistance strain gauges mounted on the automatic coupler body. The test ride was preceded by scaling of the measuring circuits by tensile and compressive forces using the bench equipment of the test laboratory of the Tikhvin Trial Centre for Railway Transport.Results. The authors obtained statistically reliable data on longitudinal forces and displacements of automatic couplers when the carriage moves in a locomotive traction passenger train.Discussion and conclusion. The authors determined the longitudinal forces and displacements of the SA-3 automatic coupler used in a locomotive traction passenger car. These data are intended for further use in bench service life testing of the automatic coupler.